2023
DOI: 10.21037/tcr-22-1912
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk and prognostic factors for intrahepatic vascular invasion in patients with hepatocellular carcinoma: a population-based study

Abstract: Background: The aim of this study was to develop nomograms to predict the risk of intrahepatic vascular invasion (IVI) of hepatocellular carcinoma (HCC) patients and estimate the overall survival (OS) and cancerspecific survival (CSS) of HCC patients with IVI. Methods:The Surveillance, Epidemiology, and End Results (SEER) database was used to identify patients with HCC from 2010 to 2015. Ultimately, 1,287 HCC patients with IVI were included in this study and randomly divided into training (n=901) and validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Early detection and diagnosis of HCC are challenging due to its aggressive nature, resulting in a majority of patients to receive treatment at advanced stages. Numerous clinical studies have revealed that the occurrence and survival of HCC are linked to various risk factors such as hepatitis B and C virus infection, excessive alcohol consumption, obesity, diabetes and fatty liver disease 4,5 . Consequently, HCC poses a significant disease burden and presents a high mortality risk, necessitating increased focus on its prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and diagnosis of HCC are challenging due to its aggressive nature, resulting in a majority of patients to receive treatment at advanced stages. Numerous clinical studies have revealed that the occurrence and survival of HCC are linked to various risk factors such as hepatitis B and C virus infection, excessive alcohol consumption, obesity, diabetes and fatty liver disease 4,5 . Consequently, HCC poses a significant disease burden and presents a high mortality risk, necessitating increased focus on its prevention and treatment strategies.…”
Section: Introductionmentioning
confidence: 99%